Mathew Guest: Neoliberal Religion: Faith and Power in the Twenty-first Century - Martikainen, Tuomas (Temenos - Nordic Journal for the Study of Religion, 2023)
Book review of Mathew Guest: Neoliberal Religion: Faith and Power in the Twenty-first Century. London: Bloomsbury, 2022, 203 pp.